Yves Saint Laurent: His Life and Times ; 5 avenue Marceau 75116 Paris - Teboul, David; Champetier, Caroline; Louvart, Hélène; Pavans de Ceccaty, Philippe (First Run Features, 2004)
His Life and Times: During the last half of the 20th century, Yves St. Laurent was the definition of French haute couture. With exclusive access to St. Laurent and his inner circle, filmmaker David Teboul outlines the influential designer's life and career, from his youth in Algeria and his selection as Christian Dior's successor at age 21, to the formation of his own world-famous firm in the 1960s. Interviewed are St. Laurent's mother and his longtime business manager and partner Pierre Berge. [www.sundancechannel.com]